An Aspect of Mahāyāna Buddhist Ethics: The Culture of Generosity (dāna) - Tashi Dorjey (Politeknik Negeri Bali, 2018)
Buddhist ethics deals with do and don’t pertaining to individual behavior by transforming inner mental process towards harmony of external phenomenon. The major ethical practices of Mahāyāna is the six perfections (pāramitā), viz. the perfection of giving or generosity, the perfection of morality, the perfection of fortitude, the perfection of effort, the perfection of concentration, and the perfection of wisdom. Dāna or generosity is the first of the six perfections, dealing with from four points of view. It can be considered to whom a generosity is given, what is to be given, how it is given, and why and with motivation it is given. In this paper I presented specifically what can be given in detailed way as traditional Buddhist texts describe generosity (dāna) in terms of the four stages. They are the generosity of material things, the generosity of freedom from fear, the generosity of spiritual teaching which entails offering comfort, concern and advice to support other’s psychological and emotional well-being, and the generosity of love.